2014
DOI: 10.2741/4220
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of macrophage autophagy induced by Salmonella enterica serovar typhi plasmid

Abstract: pR(ST98), a chimeric plasmid isolated from Salmonella enterica serovar typhi (S. typhi), is involved in bacterial multidrug-resistance and virulence, however, its exact contributions to bacterial pathogenesis are still not fully understood. To investigate whether pR(ST98) exhibits potential to mediate macrophage autophagy and apoptosis, murine macrophage-like cell line (J774A.1) was infected with wild type strain (S. typhi-WT), mutant strain (S. typhi-DeltapR(ST98)) and complement of S. typhi-DeltapR(ST98) (S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…This might contribute to evasion of immune responses by S. typhi. In addition, our previous data showed that the presence of this plasmid increases the survival of the bacterial pathogen and acts through the mitochondrial pathway to mediate macrophage apoptosis [22]. We thus suggest that pR ST98 enhances the virulence of some clinical S. typhi strains through modulating autophagy and cell death.…”
Section: Discussionmentioning
confidence: 84%
“…This might contribute to evasion of immune responses by S. typhi. In addition, our previous data showed that the presence of this plasmid increases the survival of the bacterial pathogen and acts through the mitochondrial pathway to mediate macrophage apoptosis [22]. We thus suggest that pR ST98 enhances the virulence of some clinical S. typhi strains through modulating autophagy and cell death.…”
Section: Discussionmentioning
confidence: 84%
“…Autophagy is an evolutionarily conserved, cellular degradation pathway that eliminates damaged or superfluous proteins and organelles (18,19). Cytosolic material is sequestered in autophagosomes, delivered to lysosomes for degradation, and recycled to sustain cell viability (20).…”
Section: Discussionmentioning
confidence: 99%
“…pR (ST98) has a molecular weight of 98.6 × 10 6 Da (about 159 kb), and was first identified and reported by Huang et al (2005). Subsequent studies in their laboratory have shown that mutant Salmonella, harboring a pR (ST98) plasmid deletion, inhibited autophagy in infected macrophages (He et al, 2012;Chu et al, 2014;Wu et al, 2014) and mouse embryonic fibroblasts (Lv et al, 2012), while enhancing Salmonella proliferation within cells and consequently promoting cell death. These results demonstrate that the pR (ST98) plasmid enables Salmonella to escape autophagy.…”
Section: The Escape Mechanism Employed By Salmonella To Evade Host Cementioning
confidence: 99%